Gaming Technology for Pediatric Neurorehabilitation: A Systematic Review - Iosa, Marco; Verrelli, Cristiano Maria; Gentile, Amalia Egle; Ruggieri, Martino; Polizzi, Agata (Frontiers in Pediatrics, 2022)
Introduction: The emergence of gaming technologies, such as videogames and virtual reality, provides a wide variety of possibilities in intensively and enjoyably performing rehabilitation for children with neurological disorders. Solid evidence-based results are however required to promote the use of different gaming technologies in pediatric neurorehabilitation, while simultaneously exploring new related directions concerning neuro-monitoring and rehabilitation in familiar settings. Aim of the study and methods: In order to analyze the state of the art regarding the available gaming technologies for pediatric neurorehabilitation, Scopus and Pubmed Databases have been searched by following: PRISMA statements, PICOs classification, and PEDro scoring. Results: 43 studies have been collected and classified as follows: 11 feasibility studies; 6 studies proposing home-system solutions; 9 studies presenting gamified robotic devices; 9 longitudinal intervention trials; and 8 reviews. Most of them rely on feasibility or pilot trials characterized by small sample sizes and short durations; different methodologies, outcome assessments and terminologies are involved; the explored spectrum of neurological conditions turns out to be scanty, mainly including the most common and wider debilitating groups of conditions in pediatric neurology: cerebral palsy, brain injuries and autism. Conclusions: Even though it highlights reduced possibilities of drawing evidence-based conclusions due to the above outlined biases, this systematic review raises awareness among pediatricians and other health professionals about gaming technologies. Such a review also points out a definite need of rigorous studies that clearly refer to the underlying neuroscientific principles.